2012
DOI: 10.1093/cercor/bhs402
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 and Rac3 GTPases Control Synergistically the Development of Cortical and Hippocampal GABAergic Interneurons

Abstract: The intracellular mechanisms driving postmitotic development of cortical γ-aminobutyric acid (GABA)ergic interneurons are poorly understood. We have addressed the function of Rac GTPases in cortical and hippocampal interneuron development. Developing neurons express both Rac1 and Rac3. Previous work has shown that Rac1 ablation does not affect the development of migrating cortical interneurons. Analysis of mice with double deletion of Rac1 and Rac3 shows that these GTPases are required during postmitotic inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 49 publications
(68 reference statements)
2
66
0
Order By: Relevance
“…In this direction, we have addressed the role of Rac GTPases in the development of these cells. Based on recent findings that Rac's are essential players for the correct development of cortical and hippocampal GABAergic cells in vivo (Vaghi et al, 2014; Tivodar et al, 2015; Pennucci et al, 2016), we have confirmed here that depletion of the endogenous Rac‘s impairs the neuritogenesis of interneurons in vitro .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this direction, we have addressed the role of Rac GTPases in the development of these cells. Based on recent findings that Rac's are essential players for the correct development of cortical and hippocampal GABAergic cells in vivo (Vaghi et al, 2014; Tivodar et al, 2015; Pennucci et al, 2016), we have confirmed here that depletion of the endogenous Rac‘s impairs the neuritogenesis of interneurons in vitro .…”
Section: Discussionsupporting
confidence: 86%
“…Our previous works has shown that Rac1 represented approximately 92% and Rac3 8% of total Rac proteins in P7 mouse brain (Corbetta et al, 2009). Analysis in vivo has shown that single and double Rac knockout affects the development of cortical and hippocampal interneurons (Vaghi et al, 2014; Tivodar et al, 2015; Pennucci et al, 2016). Here we have tested the effects of Rac deletion on the maturation of MGE-derived interneurons in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…58,63 The recent study by Vaghi et al (2012) investigating Rac1 and the neural specific Rac3 in the development of cortical and hippocampal GABAergic neurons suggests that both Rac1 and Rac3 contribute synergistically to the regulation of cortical and hippocampal neuronal migration and differentiation, which may explain the epileptic phenotype of the Rac1/Rac3 double mutant mice. 64,65 Lastly, several defects were also observed in the development of the cerebellum lacking Rac1. 66 Taken together, these studies clearly establish fundamental roles of RhoA, Rac1, and Cdc42 during early development of the CNS.…”
Section: Cns Developmentmentioning
confidence: 97%
“…99 In contrast, Rac3 and Rac1 appear to perform synergistic roles in the development of the nervous system as loss of both isoforms results in defects in the migration and differentiation of a number of brain cell types. [100][101][102][103] Loss of either isoform in the brain does not lead to obvious defects. 100 These results highlight that each of the Rac isoforms had been specialized for a very particular function and displays its own specific biology.…”
Section: Other Rac Isoforms: Shaping the Immune System And The Brainmentioning
confidence: 99%